Identifying Opportunities & Developing Models of Environmental Education from an Indian Perspective - Siddiqui, Tauseef ZiaIA; Pathak, Pramod (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
As we are entering in the next millennium it is essential for our experts to review the environmental education curriculum and training modules and materials, this will help in closing the gap between what environmental experts know and what the public and students needs to know. Current environmental education and training programs are stressed on controlling, remediation or clean up environmental problems. Because more than 90% of the world population growth and much of the economic growth expected in the next 40-50 years will be in developing countries it is important that environmental education must be made a priority. Therefore, teachers need continuing awareness, environmental education and related training programs to keep up with the complexity of environmental problems and technologies and strategies to reduce environmental risks. The paper focuses in developing working model of Environmental Education (EE) in the formal sector and to evaluate and statically analyze the EE knowledge perception of the different sectors of the society through structured questionnaire surveys of teachers, students and literate citizens of the urban area. This paper tries to find out the barriers and strategies for promotion of EE in India.